Diagnostic and therapeutic approach to chronic meningitis in Brazil: a narrative review - Guilherme Diogo Silva; Bruno Fukelmann Guedes; Ióri Rodrigues Junqueira; Hélio Rodrigues Gomes; José Ernesto Vidal (Arquivos de Neuro-Psiquiatria)
Background Chronic meningitis (CM) is characterized by neurological symptoms associated with the evidence of cerebrospinal fluid pleocytosis lasting > 4 weeks. Studies on the management of CM in Brazil are scarce. Objective To critically review the literature on CM and propose a rational approach in the Brazilian scenario. Methods Narrative literature review discussing the epidemiology, clinical evaluation, basic and advanced diagnostic testing, and empirical and targeted therapy for the most relevant causes of CM. The present review was contextualized with the local experience of the authors. In addition, we propose an algorithm for the management of CM in Brazil. Results In Brazil, tuberculosis and cryptococcosis are endemic and should always be considered in CM patients. In addition to these diseases, neurosyphilis and other endemic conditions should be included in the differential diagnosis, including neurocysticercosis, Baggio-Yoshinari syndrome, and endemic mycosis. After infectious etiologies, meningeal carcinomatosis and autoimmune diseases should be considered. Unbiased and targeted methods should be used based on availability and clinical and epidemiological data. Conclusion We propose a rational approach to CM in Brazil, considering the epidemiological scenario, systematizing the etiological investigation, and evaluating the timely use of empirical therapies.